2010
DOI: 10.1590/s1519-69842010000100029
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic communication and vocalization microhabitat in Ameerega braccata (Steindachner, 1864) (Anura, Dendrobatidae) from Midwestern Brazil

Abstract: Ameerega braccata is an aposematic, small dendrobatid anuran known from its type-locality, Chapada dos Guimarães, in the State of Mato Grosso, and from a few additional localities in Mato Grosso do Sul and Goiás States, Brazil. The advertisement call of A. braccata is composed of a single unpulsed note, with a frequency range from 3.5 to 4.2 KHz (N = 110), and average duration of 65.8 ms (N = 110, SD = 11.6). The territorial call is composed of five or six repeated notes, structurally similar to advertisement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…Temporal and spectral properties of anuran calls have different levels of variation ( Gerhardt, 1991 ; Gerhardt & Huber, 2002 ). Usually, in anuran species the spectral properties show low intra-individual variation and are considered static (CV < 5%), while temporal properties may have higher variation and are considered dynamic (CV > 12%) ( Márquez & Eekhout, 2006 ; Forti, Strüssman & Mott, 2010 ; Briggs, 2010 ; Morais et al, 2012 ; Carvalho et al, 2013 ; Forti, Márquez & Bertoluci, 2015 ; Forti et al, 2016 ; Köhler et al, 2017 ). The variation in acoustic properties of I. langsdorffii calls corroborates this pattern, with spectral variables presenting lower variation than temporal ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temporal and spectral properties of anuran calls have different levels of variation ( Gerhardt, 1991 ; Gerhardt & Huber, 2002 ). Usually, in anuran species the spectral properties show low intra-individual variation and are considered static (CV < 5%), while temporal properties may have higher variation and are considered dynamic (CV > 12%) ( Márquez & Eekhout, 2006 ; Forti, Strüssman & Mott, 2010 ; Briggs, 2010 ; Morais et al, 2012 ; Carvalho et al, 2013 ; Forti, Márquez & Bertoluci, 2015 ; Forti et al, 2016 ; Köhler et al, 2017 ). The variation in acoustic properties of I. langsdorffii calls corroborates this pattern, with spectral variables presenting lower variation than temporal ones.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, spectral properties, such as dominant and minimum frequency, are body size dependent ( Gingras et al, 2013 ) and related to the process of conspecific recognition, since these variables tend to be static (i.e., presenting lower intraspecific variation) ( sensu Gerhardt, 1991 ). However, temporal properties, such as call duration and pulse rate, in turn, show higher variability ( Márquez & Eekhout, 2006 ; Briggs, 2010 ; Forti, Strüssman & Mott, 2010 ; Kaefer & Lima, 2012 ; Forti, Márquez & Bertoluci, 2015 ; Forti et al, 2016 ), and are determined by social and climatic conditions ( Wong et al, 2004 ; Lingnau & Bastos, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of perches raised up off the ground by calling A. trivittata males is not a typical behavioral pattern in this amphibian family. In Cerrado savanna, for example, Forti et al (2010) observed that most Ameerega braccata called from the leaves of bushes and herbaceous plants. Haddad and Martins (1994) observed that Ameerega flavopicta usually call from rocks near streams, Ameerega hahneli from the leaf litter, and A. picta from the branches of dead trees on the leaf litter.…”
Section: Discussionmentioning
confidence: 99%
“…Ameerega braccata (Steindachner, 1864) is a colorful dendrobatid distributed in the savannah-like Cerrado ecosystem from Central and Midwestern Brazil, where it is known from localities in the States of Mato Grosso, Mato Grosso do Sul, and Goiás (Frost, 2009). A few aspects of the natural history of this species have already been addressed (Haddad and Martins, 1994;Forti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%